2021
DOI: 10.30892/gtg.38433-767
|View full text |Cite
|
Sign up to set email alerts
|

Do Indonesians Dare to Travel During This Pandemic?

Abstract: The Covid-19 pandemic that has hit the world has devastated the tourism sector. In Indonesia, the government continues to focus on bringing in tourists from various foreign countries. This study tries to explain whether Indonesian people dare to travel and what factors influence their intention to travel. We applied an explanatory quantitative approach in this study, where the survey supported online by involving 200 respondents spread throughout Indonesia. Characteristics of their age between 17 years - 60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
0
0
1
Order By: Relevance
“…Many local destinations have lost their turnover. Health awareness, subjective norms, suppression of information and scary issues, and government intervention, are believed to influence tourists' decisions to visit a destination [62][63][64][65][66].…”
Section: Figure 2 Capital In Penmentioning
confidence: 99%
“…Many local destinations have lost their turnover. Health awareness, subjective norms, suppression of information and scary issues, and government intervention, are believed to influence tourists' decisions to visit a destination [62][63][64][65][66].…”
Section: Figure 2 Capital In Penmentioning
confidence: 99%
“…Pemulihan ini bisa berhasil apabila terjadi kepercayaan publik terbangun dengan baik. Dalam pandangan wisatawan bahwa lokasi pariwisata yang aman menjadikan minat mereka untuk berkunjung lebih tinggi (Rahmawati et al, 2021). Berikutnya Rahmawati et al ( 2021) juga menyampaikan bahwa keselamatan wisatawan adalah segalanya, sehingga perlu perhatian serius dari pihak pengelola tempat wisata.…”
Section: Function Of Imageunclassified
“…There needs to be more initiatives to effectively address the waste generated from the production processes of the packaging and plastic sector, which has the potential to cause significant environmental disruption. Hence, it is imperative to implement additional waste management strategies endorsed by all stakeholders, including plastic packaging manufacturers, who can contribute through various initiatives, such as environmental accounting (Rahmawati, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Yuniarti (2017) The study conducted by Habib (2020) revealed that there exists a negative relationship between financial performance and both environmental performance and environmental costs, mediated by corporate social responsibility (CSR). Rahmawati (2012)…”
Section: Introductionmentioning
confidence: 99%